Comparison of active and passive recovery of blood lactate and subsequent performance of repeated work bouts in ice hockey players - Lau, S.; Berg, K.; Latin, R. W.; Noble, J. (The Journal of Strength and Conditioning Research, 2001)
This study examined the effect of active and passive recovery on lactate concentration and subsequent performance of repeated work bouts in 18 male NCAA Division I ice hockey players. Using a repeated measures design, subjects performed a series of skating tests before and after a 15-minute recovery. The skating test consisted of skating a course for 7 shifts, which lasted 40 seconds per shift with 90 seconds rest between shifts. Active recovery (low-intensity cycling) and passive recovery (sitting) lasted for 15 minutes and were followed by an identical 7-shift skating test. Passive vs. active recovery showed no statistically significant differences for distance skated, heart rate, or lactate. There appeared to be a trend for greater skating distance in period 2 when active recovery was used, but the difference was not significant (p > 0.05). It was concluded that active recovery did not enhance lactate removal or subsequent performance of repeated work bouts in simulated hockey play.